Conservable spatial and building elements of traditional longhouse for conservation / Janet Victoria Stia - Stia, Janet Victoria (2020)
Traditional longhouse is one of the unique communal dwellings that can be found across the globe from the Austronesia-Maritime South East Asian region to North America and ancient Ireland. Nowadays some of the longhouses abandoned and demolished to give way to modern dwellings. Some is being modernized to adapt to the latest trend of living. Traditional longhouse in Sarawak, Malaysia is no exclusion. The Dayak people which consist of three main ethnic groups namely the Iban, Bidayuh and Orang Ulu are known to be longhouse dwellers and some still strongly practicing the longhouse lifestyle. Even though the traditional way of living is still maintained, but the design, materials, and method of construction of the longhouse have been modernized from day to day. The phenomenon of abandoning, demolishing and modernizing of the traditional longhouse become a major concern which leads to this study. Objective of the study is to ascertain spatial elements of the traditional longhouse that still survived against modernization. Second objective is to identify building elements, materials, and method of construction of the existing spatial elements that has the potential to be conserved. Last objective is to develop guidelines for traditional longhouse conservation. Preliminary studies had been done to select the traditional longhouse based on the selection criteria. 15 • traditional longhouses in Sarawak were selected, which 8 longhouses in Kuching and Serian area, 2 longhouses in Saratok area and 5 longhouses in Bintulu and Kapit area. This study used qualitative data obtained from observation, drawings and photos analysis and informal non-structured interview during fieldworks. These data were recorded in Inspection Checklists to ascertain surviving spatial elements and Record Card to identify conservable building elements. Analysis was done on the percentages of traditional longhouses that still maintained the traditional spatial and building elements. Basically, longhouse has four main spatial elements that are the open veranda, long gallery, apartment, and loft. It was found that the long gallery and apartment had the highest potential to be conserved. Meanwhile, the stilts, beam-column and floor are the most conservable building elements in term of materials and method of construction. Guidelines are developed on the conservable spatial and building elements as a solution for longhouse conservation. As a conclusion, the proposed guidelines can be used by all relevant stakeholders for the conservation of traditional longhouse.